A erva-mate orgânica como estratégia de produção e reprodução social: o caso dos agricultores familiares de Ilópolis/RS - Rabaiolli, Joel Albino (2019)
The state of Rio Grande do Sul has a strong and striking culture, being recognized by the typical Gaucho figure and its customs. Chimarrão and other beverages derived from yerba mate identify the southern peoples, but besides having cultural importance, these elements are responsible for numerous knowledge that reproduces socially and perpetuates for generations. Located in the Alto Vale do Taquari, the municipality of Ilópolis / RS and adjacent areas are the largest producers of yerba mate in RS, so it is important to understand the importance of this agricultural activity to the family farmers, characterizing the production system, knowing the emergence of production and, finally, analyzing how the production of yerba mate reproduces socially. From a dialectical analysis it is sought to understand if the insertion of the production of organic yerba mate contributes to the production and social reproduction of family agriculture in Ilópolis. The area of the study has always had a strong connection with the production of yerba mate, due to the natural occurrence of the plant, and has recently adopted new production methods that have been gaining market space, such as organic production of yerba mate. To portray the organization of the production system, the existing relations and the productive processes is important to enable new studies from the yerba mate and the agents involved in the production. Geography is the fundamental role of trying to explain in a comprehensive way the determinants related to the location of phenomena, that is, geographic science seeks to present the reasons why certain elements occur on the earth, their interrelations and organization, as is the case from mate to the region of Ilópolis and Alto do Vale do Taquari. The production of organic yerba mate is a recent activity, which makes it difficult to clearly identify its influence on social reproduction in the region. Thus, it can be pointed out that organic production is an alternative to approximate production with consumption, taking into account the requirements of the market and, consequently, allowing production to continue.